Ethics of Genetic choice in Sport - Mário Rui Gomes Silva (2021)
The evolution of science and technology has made possible the improvement of highly competitive athletes ́ performance, who are now more and more athletic than ever before. However, the pursuit and the enhancement of the "best athlete" continues to be a time consuming process, which utilizes many resources and which still shows countless flaws. One way to try to overcome these restrictions is through genetic tests aimed at athletes and children and from there we can conlude whether or not individuals are fit for a particular sport. Consequently, we would know on which ones could the institutions invest in, in other words, who would benefit the most from years of training and dedication. In this review, we approach the genes related to sports activity, their role and the influence they have in an athlete's performance, as well as the current state of companies that sell this type of genetic tests to the costumer. These types of tests raise several types of ethical problems, which we divide into those that affect children and those that affect athletes, being still debatable its value comparing to conventional methods of talent identification. Testing children leaves them without an open future and narrows their autonomy. Additionally, testing athletes can lead to a forced consent and raise the risk of genetic discrimination by the institutions were they work. In this research we concluded that choosing people for a certain sport based on their genetic predisposition it is not either ethical or accurate predisposing success.